THE SALIENCY OF STAKEHOLDERS - Agus Hasan Pura A (Bina Ekonomi, 2009)
Stakeholder management is generally viewed  as a partnering between  the  firm and the who the firm considers  to its stakeholders and involves "communicating, negotiating, contracting and managing relationship"  (freeman, 2004). Managers cannot attend to all of the actual and potential claims of all the stakeholders, the issue of the "Who and What" do managers pay attention  and how  they go about making this determination are depend on stakeholders saliency. Stakeholders salience explain the condition under which managers pay attention to certain classes of stakeholders and how they prioritize stakeholder relationship. They posit that stakeholders  identification and salience is a function of managers' perceptions  of stakeholders as possessing one or more  relationships attributes  : the stakeholders'  power  influence  the organization, the legitimacy of stakeholders' relationship with  the organization,  and  the urgency  of stakeholders'  claim on  the organization.